EVALUASI PENERAPAN SISTEM KEUANGAN DESA (SISKEUDES) DALAM PENGELOLAAN KEUANGAN DESA/NEGERI DI KOTA AMBON - Linda Grace Loupatty (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to evaluate whether the implementation of Siskeudes in villages/states in Ambon City has been running effectively, and analyzes the impact of implementing Siskeudes on villages/states in Ambon City. The conceptual framework in this study uses the effectiveness theory of Walter Jack Duncan (1981) by using indicators achievement of goals, integration and adaptation are parameters to evaluate the implementation of Siskeudes in Ambon City. This research was conducted with a descriptive qualitative approach. The types of data used are primary data and secondary data. Data collection techniques are observation, interviews and documentation. The results showed that the implementation of Siskeudes in 30 villages/countries in Ambon City had been implemented well. Village financial management runs according to its procedures and provisions. Around 25 villages/countries are Leahari Country, Hutumuri Country, Rutong Country, Refinery Country, Hatalai Country, Ema Country, Hukurila Country, Naku Country, Latuhalat Country, Nusaniwe Country, Seilale Country, Urimesseng Country, Batu Merah Country, Soya Country, Village Latta, Nania Village, Waiheru Village, Halong Country, Hatiwe Besar Country, Laha Country, Rumah Tiga, Tawiri Country, Hunuth Village, Poka Village, Wayame Village have implemented village financial management procedures in an orderly and budgetary discipline. And 5 other villages, namely Negeri Amahusu, Negeri Passo, Small Hative Country, Galala Village and Negeri Lama Village, are still in the process of improving financial management to be better. In general, the implementation of Siskeudes in 30 villages/countries in Ambon City has a very positive impact, which is able to improve the performance of village financial management. It is proven that 25 villages/countries have been able to implement the Siskeudes Application although there are still many shortcomings that must be corrected. The application of Siskeudes has proven to be able to assist village officials in timely financial reporting and accountability; make the village financial management process more transparent, accountable and participatory, as well as more orderly and budgetary discipline. The Siskeudes application helps village officials in the village financial management process from the planning, implementation, administration, to reporting stages. This application is considered easy to use and has adapted to follow the development of village financial accounting principles.